Blowup Phenomena for a Modified Dullin-Gottwald-Holm Shallow Water System - Panpan Zhai; Zhengguang Guo; Weiming Wang (Abstract and Applied Analysis)
We discuss blowup phenomena for a modified two-component Dullin-Gottwald-Holm shallow water system. In this paper, some new blowup criteria of strong solutions involving the density and suitable integral form of the momentum are established.